PENINGKATAN KAPASITAS SUMBER DAYA MANUSIA DESA GUNUNG AGUNG MELALUI PRODUKSI DAN PEMASARAN DIGITAL MIE KERING SINGKONG - Danny Dermawan; Axcel Penalamenta Sk; Annisa Athaya; Bagus Yudha As’ad; Rahmi Yulistin; Erisa Febrianti; Gabriel Reinhart Siregar; Hadhistia Nur Ainun; Intan Nur Azizah; Jejaka Dwi Purnama; Meinisa; M. Maulana Syach Mufti; Septi Fiani; Unggi Clarissa; Teny Sylvia (Wisesa: Jurnal Pengabdian Masyarakat, 2024)
Gunung Agung Village faces challenges in managing human resources, especially regarding knowledge and skills in digital production and marketing. The people in Gunung Agung Village still do not make maximum use of existing commodities, especially cassava. This ignorance can be seen from the fact that many residents still directly sell their cassava harvests to factories. The cassava commodity can actually be used to make various processed products. However, there is a lack of knowledge in the community, especially in Gunung Agung Village, in utilizing cassava commodities, so that cassava commodities are only harvested and then sold to factories. Through one of the Real Work Lecture activities, an approach was made to the community by making a presentation regarding the production of Dried Cassava Noodles with digital marketing strategies. The results of this activity show an increase in knowledge and skills of human resources in Gunung Agung Village in the production of processed cassava products, as well as marketing via digital platforms. This activity also has the potential to improve people's standard of living and strengthen the competitiveness of local processed products.